Neural correlates of empathic impairment in the behavioral variant of frontotemporal dementia. Issue 6 (3rd March 2014) - Cerami, Chiara; Dodich, Alessandra; Canessa, Nicola; Crespi, Chiara; Marcone, Alessandra; Cortese, Francesca; Chierchia, Gabriele; Scola, Elisa; Falini, Andrea; Cappa, Stefano F.
Abstract: Objective: Loss of empathy is a symptom of the behavioral variant of frontotemporal dementia (bvFTD), constituting a clue for early diagnosis. In this study, we directly compared two empathy components (intention attribution [IA] and emotion attribution [EA]), correlating them with possible specific patterns of gray‐matter density reduction within the mentalizing network. Methods: We evaluated IA and EA in 18 mild bvFTD patients compared with 36 healthy controls (HCs) using a single nonverbal test. A subgroup entered a voxel‐based morphometry study. Results: Compared with HC, bvFTD patients showed IA and EA impairments. EA performance correlated with gray‐matter reduction in the right amygdala, left insula, and posterior‐superior temporal sulcus extending into the temporoparietal junction. Conclusion: We proved an empathic impairment, with the ability to infer emotional states showing the most severe deficit. These results provide further evidence of selective disease‐specific vulnerability of the limbic and frontoinsular network in bvFTD and highlight the usefulness of empathy assessment in early patients.